Perbandingan Indeks Vegetasi NDVI dan SAVI di Kebun Kelapa Sawit pada Kondisi El Nino dan La Nina - Wardana, Dimas Agung Satya; Yuniasih, Betti; Wirianata, Herry (AGROISTA : Jurnal Agroteknologi, 2023)
The extreme weather condition El Nino can cause Indonesia to experience a prolonged dry season, while La Nina causes a prolonged rainy season. These conditions affect the availability of water in oil palm plantations and affect the physiological processes of oil palm. This research aims to compare the NDVI index and SAVI index using Landsat 8 satellite imagery in the oil palm plantations of PT. Wanapotensi Guna during El Nino and La Nina. Landsat 8 satellite imagery recorded in August 2019 describes El Nino conditions and recorded in August 2020 describes La Niña conditions in the study area were downloaded from the USGS website. The NDVI and SAVI indices were analyzed using ArcGIS 10.5 software. The research results show the value of the NDVI index and SAVI index in the oil palm plantation area of ​​PT. Wanapotesi Guna has a value that is not much different in El Nino and La Nina conditions. The NDVI index value in El Nino conditions has a range of 0.07-0.46 and in La Nina conditions has a range of 0.13-0.44. Likewise, the SAVI index value in El Nino conditions has a range of 0.11-0.70 and in La Nina conditions has a range of 0.20-0.69. So it can be concluded that the NDVI index and SAVI index obtained from Landsat 8 satellite imagery cannot describe significant differences in index values ​​in oil palm plantation areas due to differences in the extreme weather conditions of El Nino and La Nina.